1989
DOI: 10.1017/s0022215100108333
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in chronic otitis media

Abstract: A statistical study was done on the sensorineural component in hearing loss, using 595 patients suffering from Chronic Otitis Media (COM); of these, 195 with monolateral COM were taken into consideration. They presented criteria of valuation which excluded other possible causes of sensorineural hearing loss, such as exposure to acoustic trauma, ototoxic drugs, cardiovascular disease, past head injury and hereditary causes. The contralateral (healthy) ear served as a control. We determined the average sensorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 28 publications
(22 reference statements)
7
28
1
Order By: Relevance
“…In the ear with SCOM, the frequency of SNHL was of 13% (15 cases). In a similar study, carried out with patients with a similar socio-economical status to those from the patients selected in the present study, SNHL was seen in 10% of the cases reviewed 12 . It is likely that SNHL associated with SCOM is higher in populations of lower socio-economic statuses 2 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the ear with SCOM, the frequency of SNHL was of 13% (15 cases). In a similar study, carried out with patients with a similar socio-economical status to those from the patients selected in the present study, SNHL was seen in 10% of the cases reviewed 12 . It is likely that SNHL associated with SCOM is higher in populations of lower socio-economic statuses 2 .…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, there was a predominance of cases of long standing ear disease, in such a way that this correlation between SNHL with a longer or shorter time of ear disease duration was limited, having seen that there were few cases with shorter times of disease duration. The correlation between SNHL and SCOM was previously shown by many authors 5,11,12 . Considering all the studies evaluated, including the one hereby presented, it is plausible to speculate that the disease duration time variation, socio-economic status and cholesteatoma present could explain the different results found.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A number of studies have suggested that sensorineural hearing loss (SNHL) may be a sequela of otitis media [6]. Various studies have demonstrated an association between chronic suppurative otitis media and SNHL [7,8]. Studies have demonstrated other auditory findings that suggest the presence of inner ear hearing loss due to CSOM [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…SOM related SNHL has been reported in 1-9% of cases [12]. In the Finnish cohort study of about 12,000 children, SOM was associated with high frequency loss (6)(7)(8) at the age of 15 years [13]. Dicroff [14] found permanent high frequency loss in few cases of SOM patient's.…”
Section: Introductionmentioning
confidence: 99%